Safety and efficacy of high‐dose tamoxifen and sulindac for desmoid tumor in children: Results of a Children's Oncology Group (COG) Phase II Study1. Issue 7 (31st December 2012) - Skapek, Stephen X.; Anderson, James R.; Hill, D. Ashley; Henry, David; Spunt, Sheri L.; Meyer, William; Kao, Simon; Hoffer, Fredric A.; Grier, Holcombe E.; Hawkins, Douglas S.; Raney, R. Beverly
Abstract Background Desmoid fibromatosis (desmoid tumor, DT) is a soft tissue neoplasm prone to recurrence despite complete surgical resection. Numerous small retrospective reports suggest that non‐cytotoxic chemotherapy using tamoxifen and sulindac may be effective for DT. We evaluated the safety and efficacy of tamoxifen and sulindac in a prospective phase II study within the Children's Oncology Group. Procedures Eligible patients were <19 years of age who had measurable DT that was recurrent or not amenable to surgery or radiation. The primary objective was to estimate progression‐free survival (PFS). Patients received tamoxifen and sulindac daily for 12 months or until disease progression or intolerable toxicity occurred. Response was assessed by magnetic resonance imaging. Results Fifty‐nine eligible patients were enrolled from 2004 to 2009; 78% were 10–18 years old. Twenty‐two (38%) were previously untreated; 15 (41%) of the remaining 37 enrolling with recurrent DT had prior systemic chemotherapy and six (16%) had prior radiation. No life‐threatening toxicity was reported. Twelve (40%) of 30 females developed ovarian cysts, which were asymptomatic in 11 cases. Ten patients completed therapy without disease progression or discontinuing treatment. Responses included four partial and one complete (5/59, 8%). The estimated 2‐year PFS and survival rates were 36% (95% confidence interval: 0.23–0.48) and 96%, respectively. All three deaths were due to progressive DT. Conclusions Tamoxifen and sulindac caused few serious side effects in children with DT, although ovarian cysts were common. However, the combination showed relatively little activity as measured by response and PFS rates. Pediatr Blood Cancer 2013; 60: 1108–1112. © 2012 Wiley Periodicals, Inc.